STRATEGI EKSISTENSI MADRASAH IBTIDAIYAH (MI) SWASTA DI TENGAH KEBIJAKAN ZONASI - Suharyadi, Aris; Isbianti, Pandit (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
In general, the popularity of madrasas, especially private madrasas, is declining due to the variety of school options that are considered more modern.  The issue of madrasas as terrorist schools and the influence of zoning policies in Indonesia have also decreased their popularity. Madrasah Ibtidaiyah is required to be able to compete with other equivalent schools in the midst of zoning policies, so it must adjust to existing changes through diverse strategies. The strategy carried out by each madrasa is certainly different and sometimes brings out unique sides. This study aims to explain how the strategy of Madrasah Ibtidaiyah Swasta (MIS) Nurul Huda, Sleman that can continue to exist today even though school competition is increasingly competitive due to zoning policies and tends to be associated with religiously sensitive issues. This research uses a qualitative approach with descriptive methods and case study types. Data collection techniques through direct observation, documentation, and in-depth interviews. The source of data obtained from the informants were: a principal, 4 class teachers, and 2 parents. Data validity using triangulation techniques, and data is analyzed using interactive steps of data collection, data reduction, data presentation, and verification or drawing conclusions.  The results of the study revealed that in general, this madrasa has a unique strategy to stay afloat. The hereditary position of the principal turns out to make the leadership aspect more mature because the school leadership understands the condition of the school very well. The motivation of the teachers in educating is very high because they have a "sense of belonging" towards MI, this is because it turns out that the majority of school residents are family, relatives, and neighbors around MI. The marketing strategy that was formed was not planned by MI, namely the mouth of word method, the social aspect of the community that is thick with one of the Islamic religious groups in Indonesia (Nahdatul Ulama) makes this MI still has its fans,  And the last is the factor of the location of schools that have few options, making parents tend to choose elementary schools that are relatively close to home.